Serum amyloid A in lung transplantation - Vietri, Lucia; Bargagli, Elena; Bennett, David; Fossi, Antonella; Cameli, Paolo; Bergantini, Laura; d’Alessandro, Miriana; Paladini, Piero; Luzzi, Luca; Gentili, Francesco; Mazzei, Maria Antonietta; Spina, Donatella; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Serum Amyloid A (SAA) is an acute phase protein and we analyzed its concentrations in lung transplantated patients (LTX). Methods: 26 LTX patients (58.6 ± 11 years) and 11 healthy controls (55 ± 11.3 years). Three groups of LTX patients: acute rejection (AR, 7) bronchiolitis obliterans syndrome (BOS, 3), acute infection (INF, 9) and stable patients (NEG, 7). Results: In LTX patients SAA concentrations were significantly increased, particularly in AR and INF. In LTX-AR patients were observed a correlation between SAA levels and peripheral CD4+ lymphocyte percentage (r=0.9, p